Analysis Study Of Paulo Freire's Thoughts And Its Application In Elementary Education - Rahayu , Hendra; Ndona, Yakobus; Gultom, Ibrahim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
The application of Freire's thinking in the context of elementary education can be seen through a dialogical and critical approach in teaching. Teachers not only convey knowledge, but also act as facilitators who help students to think critically and be actively involved in the learning process. The type of research used in this study is library research . Data sources in this library research consist of two categories: 1). Primary Data Sources: The main books written by Paulo Freire, especially Pedagogy of the Oppressed (1970). 2). Secondary Data Sources: Scientific articles, journals and research reports that discuss the application of Freire's thinking in elementary education. The results of the study show that 1). Critical Conscientization in Elementary Education is a process in which individuals understand the social and political injustices around them. 2). Dialogical Education in Elementary Education is a key element in education, where teachers and students learn from each other through two-way communication. 3). Humanistic and Inclusive Education in Elementary Education is where every student is valued as an individual who has the potential to develop, without discrimination based on social and economic background. 4). Implications for Basic Education in Indonesia are that the recently introduced independent curriculum gives teachers and students more freedom to explore subject matter flexibly, in accordance with the principles of liberating and dialogical education as taught by Freire